Genomic Evidence of an Ancient East Asian Divergence Event in Wild Saccharomyces cerevisiae. (11th January 2021) - Bendixsen, Devin P; Gettle, Noah; Gilchrist, Ciaran; Zhang, Zebin; Stelkens, Rike
Abstract: Comparative genome analyses have suggested East Asia to be the cradle of the domesticated microbe Brewer's yeast ( Saccharomyces cerevisiae ), used in the food and biotechnology industry worldwide. Here, we provide seven new, high-quality long-read genomes of nondomesticated yeast strains isolated from primeval forests and other natural environments in China and Taiwan. In a comprehensive analysis of our new genome assemblies, along with other long-read Saccharomycetes genomes available, we show that the newly sequenced East Asian strains are among the closest living relatives of the ancestors of the global diversity of Brewer's yeast, confirming predictions made from short-read genomic data. Three of these strains (termed the East Asian Clade IX Complex here) share a recent ancestry and evolutionary history suggesting an early divergence from other S. cerevisiae strains before the larger radiation of the species, and prior to its domestication. Our genomic analyses reveal that the wild East Asian strains contain elevated levels of structural variations. The new genomic resources provided here contribute to our understanding of the natural diversity of S. cerevisiae, expand the intraspecific genetic variation found in this heavily domesticated microbe, and provide a foundation for understanding its origin and global colonization history.